(untitled) (Third Sector Social Economic Review, 2019)
The aim of this study is to examine the learning style of the students who take accounting education and to examine whether the learning styles differ according to the demographic characteristics of the students. Four hypotheses were created in this direction and a questionnaire was applied to 126 students studying at Çankırı Karatekin University Faculty of Economics and Administrative Sciences. Kolb Learning Style Inventory was used as the data collection tool. Frequency, t-test and one-way analysis of variance (ANOVA) techniques were used to analyze the data obtained from the inventory. According to the research findings, it can be said that the vast majority of students have a learning style that separates and assimilates. Furthermore, it can be stated that there is no significant difference between the learning styles and gender, age and academic achievement average, but there is a significant difference according to the education program.